Mouse models of cerebral injury and cognitive impairment in hypertension - Perrotta, Marialuisa; Carnevale, Daniela; Carnevale, Lorenzo (Frontiers in Aging Neuroscience, 2023)
Hypertension is a major risk factor for dementia, including both vascular and neurodegenerative etiologies. With the original aim of studying the effect of blood pressure elevation on canonical target organs of hypertension as the heart, the vasculature or the kidneys, several experimental models of hypertension have sprouted during the years. With the more recent interest of understanding the cerebral injury burden caused by hypertension, it is worth understanding how the main models of hypertension or localized cerebral hypertension stand in the field of hypertension-induced cerebral injury and cognitive impairment. With this review we will report main genetic, pharmacological and surgical models of cognitive impairment induced by hypertension, summarizing how each specific category and model can improve our understanding of the complex phenomenon of cognitive loss of vascular etiology.